The Main Stage of Russian Managerial School’s Development - M. V. Melnik (Управленческие науки)
The article considers the issues of scientific managerial school development in the period of 60-70 years of the XX century, which incentive moments have become the holding of “Kosigin reforms”, organizational structures modernization and widening the management functions within enterprise. The concept of improving organization and national economy major link management is considered as the basic one, the main stages and enterprise system management interaction forms are defined at macro level- in regional systems, branch enterprise groups and public administration offices. The main stages of forming scientific researches in the sphere of different levels information systems management provision, automated management systems and technological processes development and production processes and management alterations structures interactions are mentioned. The role of public organizations - All-Union Society “Knowledge”, All-Union Research and Technology Societies Board in the development of management science and managerial activity at different stages is shown. The USSR cooperation development with international organizations, research and manufacture organizations of industrially developed countries at different levels of country economic development is emphasized as a factor of accelerated management system development. A special attention is paid to cadres training in the sphere of organization improvement and management technology, as well as production objects and public administration top managers.